(untitled) (Research, Society and Development, 2022)
This article aimed to characterize the manifestations of sexual harassment experienced by nursing students and investigate the strategies used after experiencing sexual harassment. To this end, a cross-sectional and descriptive research with a quantitative approach was conducted with 279 students from Nursing courses located on different municipalities and campuses of a Public Higher Education Institution in the state of Paraíba. It was observed that 59.1% of the students had already been victims of sexual harassment of the most varied forms and their main coping strategy was talking to other women about the fact. It is concluded that the identified situation requires a reflection on the urgent need for interventions to reduce and combat the occurrence of harassment in educational institutions. For this to happen, it is important to promote discussions on the subject within universities, promote an embracing and trusting environment for victims, and create concrete punishment strategies for harassers.